Investigating the role of urban vegetation alongside other environmental variables in shaping Aedes albopictus presence and abundance in Montpellier, France - Colombine Bartholomée; Paul Taconet; Mathilde Mercat; Coralie Grail; Emilie Bouhsira; Florence Fournet; Nicolas Moiroux (PLoS ONE, 2025)
Urban greening helps address urbanization challenges, but it may also favor mosquito species, vectors of pathogens causing human diseases. This study examines the relationship between urban vegetation and the presence and abundance of Aedes albopictus in Montpellier, the second greenest city of France, while accounting for meteorology, microclimate, air quality, human socio-demography, and landscape. From May to October 2023, adult mosquitoes were collected monthly in urban parks, residential areas, and the highly impervious city center using BG-Pro traps with odor and CO₂ attractants. Microclimate data (air temperature and relative humidity) were recorded on-site at each trap location using Hygrobutton data-loggers. Vegetation, land cover, meteorological, air quality, and human demographic data were gathered from open-access databases. Aedes albopictus presence and abundance were analysed according to environmental variables taken at different time lags and spatial distances using a two-stage modeling approach: bivariate analyses using generalized linear mixed models were conducted to select variables for inclusion in a multivariate random forest model, aiming to identify the factors that best explain Ae. albopictus presence and abundance. While urban vegetation had a limited effect on Ae. albopictus presence, the average patch size, and the percentage of area covered by low vegetation were among the most important predictors of abundance. The main predictors for presence were minimum hourly temperature (24h-48h before sampling), minimum atmospheric pressure during sampling, and the weekly cumulated rainfall recorded six weeks before sampling. The most important predictors of abundance were the average patch size of low vegetation, the maximum hourly temperatures during sampling, and the length of roads. To our knowledge, this is the first study examining urban vegetation’s influence on Ae. albopictus in France, offering insights for urban planning and suggesting further research on vegetation’s role in mosquito-borne disease transmission, particularly in the context of increasing dengue incidence in Europe.